2022
DOI: 10.3390/jof8101018
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Diacetylphloroglucinol Modulates Candida albicans Virulence

Abstract: The dimorphic fungus Candida albicans is one of the most important opportunistic pathogens for humankind. The use of fungicides against Candida could be associated with sub-inhibitory effects, which are referred to as fungal stress responses and are undesirable for the host. In this work, we investigated the antifungal action of 2,4-diacetylphloroglucinol (2,4-DAPG) against Candida albicans ATCC 10231 with a focus on their biofilm-forming ability. We found that 2,4-DAPG was able to reduce the ability of Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…C. albicans ATCC 10231, an opportunistic pathogen was used in this study due to its lipase-producing activity reported in the literature [ 24 , 25 , 26 , 27 , 28 ]. C. albicans was plated onto potato dextrose agar (Oxoid, ThermoFisher, MA, USA) and incubated overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…C. albicans ATCC 10231, an opportunistic pathogen was used in this study due to its lipase-producing activity reported in the literature [ 24 , 25 , 26 , 27 , 28 ]. C. albicans was plated onto potato dextrose agar (Oxoid, ThermoFisher, MA, USA) and incubated overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been demonstrated that cell surface hydrophobicity is altered by filamentation in Candida tropicalis (50). Several drugs have also been reported to reduce cell surface hydrophobicity and inhibit filamentous growth in C. albicans (51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Therefore, it is possible that there exist mechanisms that simultaneously regulate cell surface hydrophobicity and cell morphology in dimorphic yeasts and that Mar1 is involved in their regulation in Y.…”
Section: Discussionmentioning
confidence: 99%
“…The selected mutants were subjected to chemical, biochemical, and genetic analyses, and they reported three prime physiological activities relevant to DAPG sensitivity: membrane permeability, ROS regulation, and homeostasis of cells. According to Stepanov et al [ 141 ], the antifungal actions of DAPG include damaging cellular permeability, malfunctioning of H + ATPase, and disturbance of mitochondrial respiration. The primary adverse effects of DAPG are respiration intervention and ATP synthesis, leading to growth inhibition [ 142 ].…”
Section: Biocontrol Mechanisms Of Pseudomonasmentioning
confidence: 99%